Relevansi Nilai-Nilai Tarian “Raja Sine” dengan Pendidikan Nilai dalam Pembelajaran PKn Sekolah Dasar - Anna Kilu Muda; Berty Sadipun; Frumensius B. Dole (Program Studi PGSD Universitas Flores, 2020)
This stydy aims to determine the values in the Raja Sine dance that are relevant to the value education in civics learning in elementary schools. The type of cksplorratit qualitative research with the non-negative approach (culture) as atechnique for data collection is carried out by conducting in-depth interviews, documentation and participatory observation. The results showed that the values in the raja sine dance thar are relevant to the learning of civics are aesthetic values namely in class I KI 2 KD2.2, class II KI 2 KD2.2 and class III KI 2 KD2.2. the values of solidarity is in class II KI2 KD2.1. the value of togetherness (cooperation) is in class I KI 2 KD 2.3. the value of responsibility is in class I KI 2 KD2.1, class II KI 1KD2.1. the valuesof discipline is in class I KI 2 KD2.2.2, class II KI 2 KD2.2 and class III KI 2 KD 2.2.